Case Report: Long-term complete response to PSMA-targeted radioligand therapy and abiraterone in a metastatic prostate cancer patient - Parker, David; Zambelli, Jessica; Lara, Montana Kay; Wolf, Trevor Hamilton; McDonald, Amber; Lee, Erica; Abou-Elkacem, Lotfi; Gordon, Eva J.; Baum, Richard P. (Frontiers in Oncology, 2023)
Despite decades of research and clinical trials, metastatic castration-resistant prostate cancer (mCRPC) remains incurable and typically fatal. Current treatments may provide modest increases in progression-free survival but can come with significant adverse effects and are disaggregated from the diagnostic imaging needed to fully assess the spread of metastatic disease. A theranostic approach, using radiolabeled ligands that target the cell surface protein PSMA, simplifies the visualization and disease treatment process by enabling both to use similar agents. Here, we describe an exemplary case wherein a gentleman in his 70s with mCRPC on diagnosis was treated with ¹⁷⁷Lu–PSMA-617 and remains disease-free to date, over four years later.